The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1167/iovs.17-22748
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Pattern of Choroidal Thickness at the Posterior Pole in Chinese Children With Myopia

Abstract: Citation: Deng J, Li X, Jin J, et al. Distribution pattern of choroidal thickness at the posterior pole in Chinese children with myopia. Invest Ophthalmol Vis Sci. 2018;59:1577-1586. https://doi.org/10.1167 PURPOSE. To determine the relationship between choroidal thickness (ChT) at the posterior pole and refractive error and to explore the difference between the macular and peripapillary regions in children with myopia. METHODS.A total of 340 healthy Chinese children underwent a series of comprehensive ocular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
41
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 35 publications
9
41
3
Order By: Relevance
“…The SS-OCT examinations were performed by one experienced examiner from 10:00 AM to 3:00 PM each day to minimize the influence of diurnal variation. 28,29 Using this approach, the average thicknesses of the macular retinal and choroidal layers, as well as the peripapillary retinal nerve fiber layer (RNFL) and choroidal layers, were measured. The scanning protocol used a 12-line radial scan pattern that centered on the fovea and optic disc with a resolution of 1024 × 12.…”
Section: Ss-oct Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The SS-OCT examinations were performed by one experienced examiner from 10:00 AM to 3:00 PM each day to minimize the influence of diurnal variation. 28,29 Using this approach, the average thicknesses of the macular retinal and choroidal layers, as well as the peripapillary retinal nerve fiber layer (RNFL) and choroidal layers, were measured. The scanning protocol used a 12-line radial scan pattern that centered on the fovea and optic disc with a resolution of 1024 × 12.…”
Section: Ss-oct Imagingmentioning
confidence: 99%
“…In the macular region, all nine sectors of the grid were applied to analyze the average thickness; however, in the parapapillary area, only four regions of the outer circle were used to calculate the average thickness because no choroidal tissue was found in the central and inner circles, and the topographic maps were not reliable in these regions. 15,28 Retinal thickness was defined as the vertical distance between the internal limiting membrane (ILM) and the interface between the photoreceptor outer segments and retinal pigment epithelium. The RNFL thickness was defined as the vertical distance between the ILM and the interface between the nerve fiber layer and the ganglion cell layer.…”
Section: Ss-oct Imagingmentioning
confidence: 99%
“…While in the optic disc area, only four regions of the outer circle were used to analyze the average thickness, because there was no choroidal tissue in the central and inner circle, and the topographic maps were not reliable in these regions. 25 The circle placement was manually adjusted if necessary.…”
Section: Ss-oct Imagingmentioning
confidence: 99%
“…Previous studies in animals 24 and humans 58 have shown that the choroid might be capable to change its thickness in a bi-directional fashion in response and in relation to the sign of defocus already after a short period of time and in anti-phase to the axial length. Moreover, physiological 914 and defocus-manipulated circadian thickness changes 15,16 of the choroid gained more interest together with differences in the absolute thickness and distribution patterns of choroidal thickness between myopes and emmetropes 1719 . The aforementioned choroidal reaction, rhythm and global distribution therefore might serve as a predictive biomarker for future axial length development.…”
Section: Introductionmentioning
confidence: 99%